Foundations of Kurikulum Merdeka development in elementary education (from a philosophical perspective) - Abdul Rahman; Babang Robandi (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
The mismatch of philosophical foundations often causes the ineffectiveness of curriculum implementation. Ideally, the philosophical basis of a curriculum guides its implementation direction. This research examines the philosophical foundation for developing primary education curricula, particularly the Kurikulum Merdeka. The method employed Library Research by sourcing data from nationally and internationally indexed journals. This study is crucial to understanding the philosophical basis underlying the